2014
DOI: 10.7314/apjcp.2014.15.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends of Ovarian Cancer Incidence in China

Abstract: The aim of this study was to examine the trend of ovary cancer incidence from 1999 to 2010 in China and predict the burden up to 2020. Crude incidence, age specific incidence and age-adjusted incidence rates were calculated. Joinpoint regression was performed to obtain estimated annual percentages and Bayesian age-periodcohort modeling was used to predict the incidence rate until the year 2020. In China, the crude rate of ovary cancer was 7.91/100,000 and the age-adjusted rate was 5.35/100,000 overall during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 12 publications
1
38
0
4
Order By: Relevance
“…In China, the age-adjusted incidence and motility rate of ovarian cancer is 5.35 and 1.6 per 100,000, respectively (Kim et al, 2009;Wang et al, 2014). Although substantial advances in surgical techniques and chemotherapeutic treatments have been made in ovarian cancer, only approximately 30% patients with ovarian cancer can survive 5 years after the initial diagnosis (Vaughan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the age-adjusted incidence and motility rate of ovarian cancer is 5.35 and 1.6 per 100,000, respectively (Kim et al, 2009;Wang et al, 2014). Although substantial advances in surgical techniques and chemotherapeutic treatments have been made in ovarian cancer, only approximately 30% patients with ovarian cancer can survive 5 years after the initial diagnosis (Vaughan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Developed countries in West showed decreasing rate, in contrast to Asian region (Marugame and Hirabayashi, 2007;Lowe et al, 2013). In China, a significant rising trend of OC incidence, during 1999-2006 was observed and a drop happened during 2006-2010 for urban women, but a constant rise was observed in rural women (Wang, 2014) and study in Karachi, revealed stable incidence ovary cancer, but involves a relatively younger age group (Bhurgri et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…[1] China has gradually entered the aging society and ovarian cancer incidence increased year by year. [2] Its mortality rate ranked to first in gynecological tumors. The occurrence of ovarian cancer had a trend of younger in recent years.…”
Section: Introductionmentioning
confidence: 99%